2019
DOI: 10.21851/obr.43.02.201906.136
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between self-reported bruxism and torus mandibularis of patients with temporomandibular disorders

Abstract: The objective of the study was to evaluate the relationship between self-reported bruxism and torus mandibularis in patients with temporomandibular disorders (TMD). The subjects of the study were 375 patients diagnosed with TMD and 433 control patients at Chosun University Dental Hospital from November 1, 2017 to June 30, 2018. Self-reported bruxism and torus mandibularis in each group were investigated and compared statistically. Female in sex distribution and prevalence of self-reported bruxism and torus man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…TMDs cause temporomandibular joint and masticatory muscle pain and dysfunction. It primarily affects teens and 20s, and the prevalence rises with age, with women being more affected than men [1,2]. A recent domestic study also found a rapid increase in the number of patients in their 20s, but the cause is unknown [2].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TMDs cause temporomandibular joint and masticatory muscle pain and dysfunction. It primarily affects teens and 20s, and the prevalence rises with age, with women being more affected than men [1,2]. A recent domestic study also found a rapid increase in the number of patients in their 20s, but the cause is unknown [2].…”
Section: Discussionmentioning
confidence: 99%
“…Temporomandibular disorder (TMD) is a musculoskeletal disorder, and it majorly presents symptoms such as pain in the temporomandibular joint and masticatory muscles, joint noise, and mouth opening limitation. Occlusion, trauma, emotional stress, deep pain input, and parafunctional activity are known as the primary causes [1]. In recent years, the prevalence of TMDs has been steadily increasing, and the prevalence is especially high among young adults [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation